Permainan ucang-ucang angge: Refleksi nilai-nilai budaya dalam masyarakat - Mela Darmayanti; Mamat Supriatna (Universitas Indraprasta PGRI, 2025)
Traditional games are increasingly being marginalized amidst the dominance of digital games, even though these games contain cultural and educational values that are important for children's character development.. The purpose of this research is to produce an analytical description of the values contained in the traditional game Ucang-Ucang Angge. The research method uses literature study and field study. Data collection techniques were carried out through document studies, interviews, and observations. The results of this study show that the Ucang-Ucang Angge game has various values consisting of main values and supporting values. The main value in the Ucang-Ucang Angge game is the value of affection, while its supporting values include the value of togetherness, mutual trust, and mutual care. In the context of primary education, the results of this study can help teachers understand that Ucang-Ucang Angge is not just a game, but also a foundation for character education to develop students' affection and emotions.